2015
DOI: 10.6026/97320630011229
|View full text |Cite
|
Sign up to set email alerts
|

An in silico analytical study of lung cancer and smokers datasets from gene expression omnibus (GEO) for prediction of differentially expressed genes

Abstract: Smoking is the leading cause of lung cancer development and several genes have been identified as potential biomarker for lungs cancer. Contributing to the present scientific knowledge of biomarkers for lung cancer two different data sets, i.e. GDS3257 and GDS3054 were downloaded from NCBI׳s GEO database and normalized by RMA and GRMA packages (Bioconductor). Diffrentially expressed genes were extracted by using and were R (3.1.2); DAVID online tool was used for gene annotation and GENE MANIA tool was used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
(35 reference statements)
2
12
0
Order By: Relevance
“…Finally, the survival curve analysis of 10 upregulated genes using TCGA data indicated that high www.nature.com/scientificreports www.nature.com/scientificreports/ expression of HSP90AA1, RAC1 and CDKN1A induced by GaAs was clearly related to the lower survival probability in LUAD or LUSC patients. HSP90AA1 was found to be directly associated with lung cancer 34 . The overexpression of Rac1 was linked to aggressive growth and other malignant characteristics of tumours, and a high level of Rac1 could predict a poor prognosis in different types of cancer 35 .…”
Section: Discussionmentioning
confidence: 97%
“…Finally, the survival curve analysis of 10 upregulated genes using TCGA data indicated that high www.nature.com/scientificreports www.nature.com/scientificreports/ expression of HSP90AA1, RAC1 and CDKN1A induced by GaAs was clearly related to the lower survival probability in LUAD or LUSC patients. HSP90AA1 was found to be directly associated with lung cancer 34 . The overexpression of Rac1 was linked to aggressive growth and other malignant characteristics of tumours, and a high level of Rac1 could predict a poor prognosis in different types of cancer 35 .…”
Section: Discussionmentioning
confidence: 97%
“…The first data set GDS3837 provides insight into potential prognostic biomarkers and therapeutic targets for non-small cell lung carcinoma, where it has 54674 genes, 60 normal and 60 tumor samples that are taken from nonsmoking females [23, 24]. The second data set GDS3257 provides insight into the molecular basis of lung carcinogenesis induced by smoking, where it has a total of 22283 genes, and contains 107 samples that are taken from former, current and never smokers [23, 24], where GDS3837 and GDS3257 can be downloaded from NCBI’s GEO Database.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the reliability of the MG-PCC and t-SNE-SSP, we applied them to gene expression data sets of lung cancers [23, 24]. Results showed that MG-PCC algorithm was able to put tumor and normal samples into their respective mini-groups, and t-SNE-SSP maps gave these mini-groups clear boundaries also, which helped us to mine the subtypes of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…While the expression of GPM6A is never above 5 among early-stage cancer patients, among 28.1% of late-stage patients its expression is above 5. GPM6A has been suggested to be a biomarker in colon and lung cancers (Camps et al, 2009;Hasan et al, 2015).…”
Section: S2 Application Using Colon Cancer Microarray Datamentioning
confidence: 99%